2014
DOI: 10.4322/rbcv.2014.375
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação da membrana de látex natural e do extrato da pele de rã (Lithobates catesbiana) em feridas cirúrgicas cutâneas de ratos Wistar

Abstract: ResumoImplantou-se a membrana de látex natural e o extrato da pele de rã individualmente e em conjunto em feridas cutâneas de ratos com o intuito de se avaliar o processo de reparação tecidual e possíveis complicações. Utilizaram-se 60 ratos da linhagem Wistar divididos em grupos experimentais: grupo controle (GC), grupo membrana de látex (GM), grupo óleo do extrato da pele de rã (GO) e grupo membrana de látex e óleo de rã (GMO), cada um com 15 animais. Aos três, cinco, sete, 14 e 21 dias de pós-operatório, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The results obtained after the appliance of the macroporous biomembrane, in the present study, were similar to the ones described previously 46 , using the latex biomembrane of H. brasiliensis in surgical cutaneous wounds in Wistar rats. These authors also observed the prevention of crust formation during all phases of the healing process and the visual aspect of the lesion with the formation of a viscous layer protecting and maintaining the moisture of the wound.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained after the appliance of the macroporous biomembrane, in the present study, were similar to the ones described previously 46 , using the latex biomembrane of H. brasiliensis in surgical cutaneous wounds in Wistar rats. These authors also observed the prevention of crust formation during all phases of the healing process and the visual aspect of the lesion with the formation of a viscous layer protecting and maintaining the moisture of the wound.…”
Section: Discussionsupporting
confidence: 91%